The Effect of Compensation on Enhancing Employee Performance - Bachtiar Arif, Bachtiar; Romadhoni, Moh. Gufron; Tanjung, Rosdiana Imroati Kurnia; Wibowo, Teguh; Al-Amin, Al-Amin (International Journal of Sharia Business Management, 2024)
This research was conducted with the main objective of identifying the influence of compensation on employee performance at PT Citra Sejati Lestarindo in Bekasi. The research method used is explanatory research, which aims to explain the cause-and-effect relationship between the compensation variable and employee performance. A sample of 68 respondents was taken from the company, using statistical analysis techniques such as regression, correlation, determination, and hypothesis testing. The results of this research show that the compensation variable, expressed in an average score of 3.74, falls within the "good" criteria according to the scale range used in this study. Similarly, the employee performance variable, which obtained an average score of 3.79, also falls within the "good" criteria. This indicates that the majority of respondents view the compensation provided by the company as adequate and having a positive impact on employee performance. Regression analysis shows that compensation has a significant influence on employee performance, with the regression equation Y = 13.242 + 0.658X. A correlation value of 0.754 indicates a strong relationship between the two variables, with the contribution effect of compensation on employee performance reaching 56.9%. The hypothesis test also yielded a t count significantly greater than the t table value, and a significance level smaller than the alpha set, thus accepting the hypothesis that compensation has a positive and significant effect on employee performance statistically. Based on the results of this research, it is recommended that the company maintain and improve its already good compensation policies, and empower employees through the implementation of good regulations and more intensive motivation, in order to continue improving employee performance and satisfaction in the future.